Disaster Agriculture and Media - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Technical Centre for Agricultural and Rural Cooperation, 2010)
Mass communication is one of the most important post-disaster assets that can be available to an affected population. The main-stream media, when it does cover a major natural disaster, oftentimes does well at providing details of what happened.